Comparison of hypoglycemic effects of polysaccharides from four legume species. (May 2019) - Wu, Guang-Jie; Liu, Dan; Wan, Yu-Jun; Huang, Xiao-Jun; Nie, Shao-Ping
Abstract: Four legume polysaccharides were extracted from mung bean (MBP), azuki bean (ABP), pea (PP) and cowpea (CPP) with obvious differences in molecular weight and monosaccharide composition. Their hypoglycemic activities in STZ-induced diabetic mice were compared by oral administration at the dose of 400 mg/kg·bw/d. The analysis of fasting blood glucose (FBG), fasting serum insulin (FINS), serum lipids (including total cholesterol, triglyceride, high density lipoprotein cholesterol, low density lipoprotein cholesterol), hepatic glycogen content and mice body weight showed that ABP and CPP possessed significant hypoglycemic activities. Histopathological observation confirmed the capability of ABP and CPP to intervene the damage in pancreas tissues. Results suggested that the hypoglycemic effects of the four kinds of legume polysaccharides were significantly different, which might due to their different chemical structures. Graphical abstract: Image 1 Highlights: The molecular structure of four legume polysaccharides is different. Polysaccharides from azuki bean and cowpea has hypoglycemic effect. Polysaccharides from mung bean has little hypoglycemic effect.